(untitled) (Revista Iberoamericana de Bioética, 2026)
Nursing staff specialized in critical care for COVID-19 patients play a fundamental role in providing emotional and human support, improving the quality of life of patients and alleviating their suffering, which contributes to successful treatment. Objective: to analyze the bioethical principles applied by nursing staff in the care of COVID-19 patients in the intermediate care unit (INCU) and intensive care unit (ICU). Methodology: interpretative phenomenological approach and semi-structured in-depth interview with eight nurses who cared for COVID-19 patients in the ICU and INCU (first and second wave) in Hospitals of the Ministry of Health and EsSalud, selected on the grounds of convenience. Results: they applied bioethical principles prioritizing beneficence, and distributive justice in terms of resources, seeking the well-being of critical care patients; in some cases violating the principle of autonomy.